Optimisation of the WhatsApp Application in Learning Taḥsīn al-Qur'ān To Improve Students Reading al-Qur'ān Ability - Suwarno Suwarno; Ismet Nur; Rahmanita Zakaria; Evanirosa Evanirosa (STAI Hubbulwathan Duri, 2022)
AbstractAccording to the Ministry of Education, Culture, Research and Technology circular, learning for the academic year 2021/2022 can be carried out face-to-face. However, at IAIN Takengon, face-to-face learning is only held for new students, while students still carry out lectures boldly. In learning challenges, many media are used by lecturers, one of which is the WhatsApp application. Including the Taḥsīn al-Qur'ān course using the WhatsApp application. This study aims to determine the optimisation and effectiveness of the use of the WhatsApp application in Taḥsīn al-Qur'ān learning to improve students' reading Qur'an ability.This research uses mixed research methods (mixed methods study). The data collection technique was carried out using interview and observation techniques with students through zoom meetings and google meet to find qualitative data. In contrast, quantitative data were collected through documentation techniques. Analysis of the data used is also qualitative data analysis and quantitative analysis; qualitative analysis is used to analyse data from interviews and observations of optimising WhatsApp applications in bold learning, while quantitative data analysis is used to analyse the analysis of students' reading ability of the Qur'ān related to the use of the WhatsApp application. in learning Taḥsīn al-Qur'ān.The study results in optimising the WhatsApp application were carried out by maximising the use of features or menus in the WhatsApp application. The use of the WhatsApp application in Taḥsīn al-Qur'ān learning to improve students' reading of the Qur'ān is quite effective based on the results of the t-test of the pretest and post-test scores where the value of t table with a significant degree of 0.05 and df=16 is obtained t_count=9.419. Because t_countt_table (9,141,746